2013
DOI: 10.1371/journal.pone.0072457
|View full text |Cite
|
Sign up to set email alerts
|

Total Protein Analysis as a Reliable Loading Control for Quantitative Fluorescent Western Blotting

Abstract: Western blotting has been a key technique for determining the relative expression of proteins within complex biological samples since the first publications in 1979. Recent developments in sensitive fluorescent labels, with truly quantifiable linear ranges and greater limits of detection, have allowed biologists to probe tissue specific pathways and processes with higher resolution than ever before. However, the application of quantitative Western blotting (QWB) to a range of healthy tissues and those from deg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
275
2
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 348 publications
(293 citation statements)
references
References 26 publications
(32 reference statements)
14
275
2
2
Order By: Relevance
“…This is further complicated by the fact that some detection methods, in particular enhanced chemiluminescence using x-ray film, have a very restricted linear range, and careful attention to the experimental conditions is necessary to ensure linearity. It is typically better to normalize Western blots using total protein loading as the denominator (3)(4)(5)(6)(7)(8)(9)(10)(11). To avoid potential pitfalls and with a focus on improving transparency, the JBC strongly recommends that authors describe their methods used to quantify signal intensity, how the linearity of signal intensity with antigen loading was established, and how protein loading was normalized between lanes.…”
Section: Presentation and Quantitation Of Western Blotsmentioning
confidence: 99%
“…This is further complicated by the fact that some detection methods, in particular enhanced chemiluminescence using x-ray film, have a very restricted linear range, and careful attention to the experimental conditions is necessary to ensure linearity. It is typically better to normalize Western blots using total protein loading as the denominator (3)(4)(5)(6)(7)(8)(9)(10)(11). To avoid potential pitfalls and with a focus on improving transparency, the JBC strongly recommends that authors describe their methods used to quantify signal intensity, how the linearity of signal intensity with antigen loading was established, and how protein loading was normalized between lanes.…”
Section: Presentation and Quantitation Of Western Blotsmentioning
confidence: 99%
“…3B). Moreover, a previous study reported no signs of toxicity or any apparent differences in cellular growth rate, even after transduction with higher MOIs (data not provided) [13].…”
Section: Pls3 Protein Levels In Hek293t Cells Transduced With Lv-pls3mentioning
confidence: 85%
“…Ideally, SMA pathophysiology should be studied in in vitro cultures of primary MNs [10,15,18,23]. However, due to decreased MN culture yields, the NSC-34 cell line is considered a suitable alternative to MN cultures and has been widely used to model MN diseases [13]. Indeed, NSC-34 MN-like cells differentiate via a process resembling that of primary MNs, comprise extended neurites, and express MN-specific markers [4].…”
Section: Discussionmentioning
confidence: 99%
“…The membranes were blocked and probed using a 1:2,500 dilution of anti-HA monoclonal antibody in blocking buffer (Thermo Fisher, Pittsburgh, PA), followed by a 1:30,000 dilution of horseradish peroxidase-conjugated goat anti-rabbit antibody (69). Densitometry of Coomassie-stained SDS-PAGE gels was used to standardize the Western blots using total protein analysis, as described previously (70,71). Detection was performed using the ECL Plus kit (Thermo Fisher) and chemiluminescence detection (ProteinSimple, Santa Clara, CA).…”
Section: Methodsmentioning
confidence: 99%